a ANALISA BAKTERI Escherichia coli DENGAN METODE MOST PROBABLE NUMBER (MPN) PADA CINCAU HITAM YANG BEREDAR DI PASARAN - kurniawan, rudi erwin (Fakultas Kedokteran, Institut Kesehatan Deli Husada Deli Tua, 2024)
Black grass jelly is a popular food, used as an ingredient to mix food and drinks. Black grass jelly can also be used in medicine such as lowering internal heat, mouth ulcers, fever, stomach pain, and preventing indigestion to be useful in lowering blood pressure. Black grass jelly is sold in traditional markets, but the presentation and processing of black grass jelly often lacks hygiene or hygiene. Unhygienic storage places such as being placed in open containers result in easy exposure to dust and are easily infested with flies. Disease-causing microbes attach to unclean body skin, which then allows them to attach to food which is a way of mechanical transmission. The bacteria that often contaminate food are Escherichia coli bacteria. Some of the health problems caused by Escherichia coli bacteria include meningitis, urinary tract infections, diarrhea and sepsis. This study aims to determine the presence of Escherichia coli bacterial contamination in black grass jelly circulating in the Lubuk Pakam market, and then count the number of colonies that grow on EMBA media. The method used in this research is descriptive with the MPN test.The results of the research on black grass jelly showed the presence of Escherichia coli bacteria. It was concluded that a positive result was obtained on EMBA media contaminated with Escherichia coli bacteria characterised by the presence of metallic green colonies.